Revealing the Satellite DNA History in Psalidodon and Astyanax Characid Fish by Comparative Satellitomics - Goes, Caio Augusto Gomes [UNESP]; dos Santos, Rodrigo Zeni [UNESP]; Aguiar, Weidy Rozendo Clemente [UNESP]; Alves, Dálete Cássia Vieira; Silva, Duílio Mazzoni Zerbinato de Andrade [UNESP]; Foresti, Fausto [UNESP]; Oliveira, Claudio [UNESP]; Utsunomia, Ricardo; Porto-Foresti, Fabio [UNESP] (Frontiers, 2022)
Eukaryotic genomes are usually enriched in repetitive DNA sequences, which can be classified as dispersed or tandemly repeated elements. Satellite DNAs are noncoding monomeric sequences organized in a head-to-tail fashion that are generally located on the subtelomeric and/or pericentromeric heterochromatin. In general, a single species incorporates a diverse group of satellite DNA families, which collection is called satellitome. Here, we characterized three new satellitomes from distinct characid fish (Psalidodon fasciatus, P. bockmanni, and Astyanax lacustris) using a combination of genomic, cytogenetic, and bioinformatic protocols. We also compared our data with the available satellitome of P. paranae. We described 57 satellite DNA (satDNA) families of P. fasciatus (80 variants), 50 of P. bockmanni (77 variants), and 33 of A. lacustris (54 variants). Our analyses demonstrated that several sequences were shared among the analyzed species, while some were restricted to two or three species. In total, we isolated 104 distinctive satDNA families present in the four species, of which 10 were shared among all four. Chromosome mapping revealed that the clustered satDNA was mainly located in the subtelomeric and pericentromeric areas. Although all Psalidodon species demonstrated the same pattern of clusterization of satDNA, the number of clusters per genome was variable, indicating a high dynamism of these sequences. In addition, our results expand the knowledge of the As51 satellite DNA family, revealing that P. bockmanni and P. paranae exhibited an abundant variant of 39 bp, while P. fasciatus showed a variant of 43 bp. The majority of satDNAs in the satellitomes analyzed here presented a common library repetitive sequence in Psalidodon and Astyanax, with abundance variations in each species, as expected for closely related groups. In addition, we concluded that the most abundant satDNA in Psalidodon (As51) passed through a diversification process in this group, resulting in new variants exclusive of Psalidodon.
Keywords: characiforms; fish; neotropical fishes; satDNA evolution; satellitome